21st August: 14th Sunday after Pentecost - Nixon, David (The expository times, 2016)
The article focuses on the Cheerio challenge based on stacking of breakfast cereals Cheerios by fathers on their babies when they are asleep. Topics discussed include idea of the Cheerio challenge from Life Of Dad social network; the Cheerio challenge as means of evaluating the parenting by fathers; and relation development between father and child via the challenge.